Ultrasonic implantation and imaging of sound-sensitive theranostic agents for the treatment of arterial inflammation - Su, Xiaoqian (2021)
For site-specific diseases such as atherosclerosis, it is desirable to noninvasively and locally deliver therapeutics for extended periods of time. High-intensity focused ultrasound (HIFU) provides targeted drug delivery, yet remains unable to sustain delivery beyond the HIFU treatment time. Furthermore, methods to validate HIFU-enhanced drug delivery remain limited. In this study, we report on HIFU-targeted implantation of degradable drug-loaded sound-sensitive multicavity PLGA microparticles (mcPLGA MPs) as a theranostic agent for the treatment of arterial lesions. Once implanted into the targeted tissue, mcPLGA MPs eluted dexamethasone for several days, thereby reducing inflammatory markers linked to oxidized lipid uptake in a foam cell spheroid model. Furthermore, implanted mcPLGA MPs created hyperechoic regions on diagnostic ultrasound images, and thus noninvasively verified that the target region was treated with the theranostic agents. This novel and innovative multifunctional theranostic platform may serve as a promising candidate for noninvasive imaging and treatment for site-specific diseases such as atherosclerosis.